Recycling perception and practice in Shah Alam municipality - Azmi, Norazrina (2018)
Fast growth in the populace, development and technology has caused the increasing sum of municipal solid waste in Malaysia. Solid waste is one of the conservational issues that have to be encountered by communities. Recycling is the effective ways to overwhelm this issues. Not more than 5% of the total solid waste produced in Malaysia is being reused despite the massive public expenditure allocated on recycling campaigns. Thus, with this view, a preliminary investigation is required to be done, which is the main focus of this research. The scope of research focused on the solid waste management in Shah Alam municipality. Precisely, the research was focused on the recycling perception and practices in their daily life. A questionnaire was developed to determine perception and practice of recycling. The survey were being distributed manually and by spreading the link from google.docs to the Shah Alam’s resident. The data collected are analyzed using statistical analysis, minitab software. The result showed that, majority of the Shah Alam’s resident aware and believe that recycling is important. However, low participation of respondent’s on recycling practice despite the fact that high percentage of respondent is knowledgeable on how to recycle solid waste. Results was tested using Chi square test and it shows that there is significant relationship (p<0.05) between gender and awareness about solid waste recycling. Analysis also displays there is relationship between gender and knowledge level on how to recycle solid waste but there is no relationship between level of education with knowledge level on how to recycle solid waste since the (p>0.05). Next, result showed that level of education has effect on respondent’s perception of importance of recycling practice and it found that respondents who have education tends to believe that recycling is important. In Shah Alam municipality, majority of respondents participate in recycling practice due to environmental concern, followed by convenient and economic incentives. Result of the survey showed that lack of awareness about the recycling program and very few educational program about recycling are two mains barriers to sustainable recycling in Shah Alam. This research study found that, more convenient location for bins is the most potential strategy to promote recycling activities which have highest percentage followed by re-education about the recycling initiative. Most respondents show their neutrality on level of satisfaction with the frequency of recyclable collection service and level of satisfaction towards public engagement in decision in relation to recycling planning process in the city.